High frequency power supply to improve operation stability of linear electron accelerator (Nexo Revista Científica, 2021)
The use of linear electron accelerators in medicine and industry is explained by the simplicity of the input and output of accelerated electrons and adjusting the energy and dose rate, as well as the high dose rate of bremsstrahlung. The purpose of this work is to increase the stability of their work. A standing wave accelerator containing a high-frequency generator, a phase shifter, a waveguide bridge, a high-frequency load, and an accelerating system of two accelerating sections is equipped with two waveguide tees. Their inputs are connected to the output arms of the waveguide bridge, and the first and second output arms of each tee are connected to the first and last accelerating cells of each section, respectively. In this system, due to the introduction of several elements that do not require large costs for manufacturing and tuning, a significantly greater frequency separation of the operating mode of oscillations from neighboring ones is ensured, or even a single-frequency excitation mode is implemented, which makes it possible to significantly increase the stability of the accelerator operation. This technique can be used to increase the stability of operation in the design and calculation of linear accelerators of electrons with a standing wave.